O medronheiro : da diversidade à ecologia - Ribeiro, M.M.A. (2016)
Fifteen strawberry tree natural populations in different ecological conditions were sampled, ca. 30 trees per stand. Our aims were to investigate the genetic structure the species, and to disclose the historical demographic processes shaping the genetic structure. The obtained information will be used in the species improvement and in the design and management of conservation programs. Fifteen haplotypes were obtained after screening the individuals with four chloroplast microsatellites. Four clusters were identified using BAPS analysis. A “northern”, a “central”, a “southern”, and a four cluster with a single population. The hierarchical AMOVA showed a stronger differentiation among clusters than among populations within clusters. The relatively low among populations within clusters differentiation could be explained by the common postglacial history of nearby populations, which might also be connected through bird-mediated seed flow. The species was also ecologically characterized in the Centre region, using bioclimatology, lithology, topography, soil type, vegetation and wildfires records. The data processed was the digital terrain model (DTM), mapping soils, burnt areas perimeters and phytosociological and biogeographical maps. Climatological data was used to calculate bioclimatic indices. Exploratory multivariate statistical analysis with the gathered data was performed: a principal component analysis (PCA) and hierarchical cluster analysis (HCA). Finally, the Habitat Suitability for the species was calculated using the Analytic Hierarchy Process (AHP).